Evaluation of Teacher Professional Development: International Experiences and Recommendations for Vietnam - Hoang Doan Huy, Nguyen; Hai, Pham Thi Thanh (VNU Journal of Science: Education Research; Vol 39 No 2, 2023)
Teacher professional development is considered as one of the important stages of improving the quality of education; Accordingly, teacher professional development assessment also needs to be researched and applied effectively to ensure its contribution to the improvement of teachers’ quality. This study uses the document analysis based on international articles retrieved from databases such as ScienceDirect, Scopus, Google Scholar on the issue of teacher professional development assessment. Research results show that a number of works have proposed assessment standards, assessment forms and other recommendations necessary to help not only recognize the results of professional development that teachers achieve, thereby helping to further improve the respective professional development process. The analysis also shows that there is currently a major shortage in the development and validation of teacher professional development assessment toolkits, especially in the context of Vietnam. Based on the observations related to international practice on assessment and development of instruments to evaluate teacher professional development, the study proposes a number of recommendations to develop Vietnamese teacher professional development evaluation instruments.